Preparation method of acrylate copolymer

By preparing thiol modified acrylonitrile and combining specific monomers, the block copolymer structure is formed by using a segmented addition process, which solves the problem of unbalanced hardness and toughness of acrylate copolymers, and significantly improves thermal stability and aging resistance.

CN119490618AInactive Publication Date: 2025-02-21SHANDONG HETIANXIA NEW MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510076453.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-02-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing acrylate copolymers are difficult to achieve a balance of hardness and toughness, and the thermal stability and aging resistance are insufficient.

Method used

By preparing thiol modified acrylonitrile, combined with monomers such as styrene, methyl methacrylate and butyl acrylate, a block or gradient copolymerization structure is formed by adding emulsifiers and initiators in segments.

Benefits of technology

The balance between polymer hardness and toughness is achieved, and the thermal stability and aging resistance are significantly improved, and the impact resistance reduction caused by excessive rigidity is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a preparation method of an acrylate copolymer, and belongs to the technical field of high polymer materials, and the preparation method comprises the following steps: step S1, preparation of thiol modified acrylonitrile: adding acrylonitrile and o-aminobenzenethiol into a solvent, then adding azodiisobutyronitrile, in a nitrogen environment, heating, stirring, settling and washing to obtain thiol modified acrylonitrile; drying to obtain mercaptan modified acrylonitrile; step S2, preparation of an acrylate copolymer: adding water and a first emulsifier into a reaction kettle, heating and stirring, adding styrene and a first initiator, then adding methyl methacrylate, butyl acrylate, a second emulsifier and a second initiator, keeping the temperature unchanged, and continuing stirring to obtain the acrylate copolymer; and finally adding mercaptan modified acrylonitrile, a third emulsifier and a third initiator, continuously stirring to obtain an acrylic copolymer emulsion, and carrying out spray drying to obtain the acrylate copolymer. According to the invention, balance of hardness and toughness of the copolymer and improvement of thermal stability and aging resistance are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a method for preparing an acrylate copolymer. Background Art

[0002] Acrylate copolymers are copolymers of acrylate monomers and other vinyl monomers obtained by emulsion polymerization. By selecting different monomers, production processes and compounding methods, acrylic resin copolymers of various types and properties can be synthesized and then applied to different fields. For example, acrylate copolymers are commonly used in water-based coatings, automotive coatings, industrial coatings and other fields. They can also be used in textiles, plastic products and other fields to provide waterproof, anti-fouling, UV resistance and other properties, which can not only improve the appearance quality of the product, but also improve its durability.

[0003] The Chinese patent document with the announcement number CN114591474B discloses a highly resilient water-based acrylic ester composition and its preparation method, wherein the composition is an ABC triblock structure, wherein A is polymerized from a composition of acrylic ester and at least one of acrylic acid, β-acryloxypropionic acid, and methacrylic acid; B is polymerized from a composition of acrylic ester and a polyvinyl crosslinking monomer; C is polymerized from a composition of styrene or styrene and acrylonitrile; A monomer accounts for 10-30wt% of the total polymerized monomer mass, B monomer accounts for 60-85wt%, and C monomer accounts for 5-20wt%. The composition is polymerized into a copolymer of the ABC triblock structure by RAFT emulsion technology, and after the obtained acrylic ester composition emulsion is formed into a film, the film not only has high breaking strength and high breaking elongation, but also greatly improves the resilience of the film, but fails to solve the problem of insufficient thermal stability and aging resistance of the acrylic ester copolymer.

[0004] At present, most acrylic copolymers have difficulty in achieving a balance between hardness and toughness. They are unable to meet the hardness requirements while also meeting the toughness requirements, or they are too flexible so that the rigidity and hardness do not meet the requirements.

[0005] Therefore, it is necessary to provide a method for preparing an acrylate copolymer to solve the problems existing in the above-mentioned prior art. Summary of the invention

[0006] In view of this, the present invention provides a method for preparing an acrylate copolymer, which can achieve a balance between the hardness and toughness of the polymer and improve the thermal stability and aging resistance.

[0007] The specific scheme of the present invention is as follows: a method for preparing an acrylic ester copolymer comprises the following steps: Step S1, preparation of mercaptan-modified acrylonitrile: Adding acrylonitrile and o-aminobenzenethiol to a solvent, and then adding azobisisobutyronitrile, heating and stirring under a nitrogen environment, settling, washing, and drying to obtain mercaptan-modified acrylonitrile; Step S2, preparation of acrylate copolymer: Add water and the first emulsifier into a reaction kettle, heat up and stir, add styrene and the first initiator, then add methyl methacrylate, butyl acrylate, the second emulsifier and the second initiator, keep the temperature constant and continue stirring, finally add thiol-modified acrylonitrile, the third emulsifier and the third initiator, continue stirring to obtain an acrylic copolymer emulsion, spray dry and obtain an acrylate copolymer.

[0008] The benzene ring in styrene is a rigid group, which can improve the mechanical strength and thermal stability of the copolymer, increase the glass transition temperature of the copolymer, and give the copolymer a higher heat deformation temperature. The methyl methacrylate skeleton has a high density of CC bonds, which gives the copolymer higher hardness, scratch resistance and impact resistance. In addition, methyl methacrylate is relatively stable under the action of ultraviolet light and oxygen, which reduces the aging rate of the polymer. The long-chain alkyl structure of butyl acrylate has a large free rotation ability, which reduces the rigidity of the polymer molecular chain and improves flexibility. At the same time, it reduces the glass transition temperature of the copolymer, improves the toughness of the polymer at low temperatures, and significantly improves the impact resistance of the polymer, which can avoid the problem of reduced impact resistance of the copolymer due to excessive rigidity.

[0009] By introducing o-aminobenzenethiol, mercaptan-modified acrylonitrile is obtained, which adds amino and mercaptan functional groups to the acrylonitrile molecular structure, thereby giving the modified acrylonitrile higher reactivity and more functional sites, making the modified acrylonitrile more compatible and reactive with other monomers (such as styrene, acrylate, etc.) in subsequent copolymerization reactions. The presence of amino and mercaptan enhances the cross-linking ability of the modified acrylonitrile and improves the interaction between molecular chains, thereby improving the heat resistance and chemical corrosion resistance of the copolymer.

[0010] By adopting the process of adding emulsifiers in stages, the emulsifiers are divided into the first emulsifier, the second emulsifier and the third emulsifier, and added three times, the emulsion stability in the early, middle and late stages of the reaction is guaranteed, the monomer or polymer stratification is prevented, and the overall uniform distribution of the latex is promoted, which helps to improve the physical properties of the copolymer. The addition of the initiator also adopts a segmented process. The initiator is divided into the first initiator, the second initiator and the third initiator, and added three times, which is conducive to the continuous reaction at different stages and avoids the problem of too fast or uneven reaction rate caused by adding the initiator at one time. By gradually adding different monomers (styrene, methyl methacrylate, butyl acrylate, etc.), a block or gradient copolymer structure is formed, giving the polymer more excellent performance, which helps to improve the stability and aging resistance of the copolymer.

[0011] Preferably, in step S1, the heating and stirring temperature is 55-65° C., the speed is 300-400 r / min, and the time is 23-25 ​​h; and the solvent is dimethyl sulfoxide.

[0012] Preferably, the ratio of the first emulsifier, the second emulsifier and the third emulsifier is (7-8): (1-1.5): (1-1.5).

[0013] Preferably, the ratio of the first initiator, the second initiator and the third initiator is (5-6): (2.5-3.5): (1.5-2.5).

[0014] Preferably, in step S2, the first emulsifier, the second emulsifier and the third emulsifier are all one of sodium dodecyl sulfate and sodium dodecylbenzene sulfonate; the first initiator, the second initiator and the third initiator are all one of potassium persulfate, sodium persulfate and ammonium persulfate.

[0015] Preferably, in step S2, the temperature of the heating and stirring is 75-80°C, the speed is 350-450r / min, and the time is 2-3h; the speed of continued stirring is 300-400r / min, and the time is 3-5h.

[0016] Preferably, in step S2, ethyl 3-aminocrotonate is added before continuous stirring; the continuous stirring speed is 250-350 r / min, and the time is 2-3 h.

[0017] The ester group in 3-amino ethyl crotonate can reduce the glass transition temperature of the polymer, thereby improving the flexibility of the polymer. At the same time, the amino group can form hydrogen bonds with other molecules, etc., which enhances the interchain force and improves the strength of the polymer, so that the polymer exhibits a higher balance of strength and toughness. The amino group can also provide active sites for cross-linking reactions, react with carboxyl groups and other groups to form cross-linked structures, and significantly improve the heat resistance and mechanical properties of the polymer. In addition, the amino and ester groups in 3-amino ethyl crotonate provide good antioxidant properties, which can inhibit the degradation of the polymer by ultraviolet light or oxygen, and make the copolymer have a longer service life.

[0018] Preferably, in step S2, the spray drying temperature is 200-210°C.

[0019] Preferably, the following raw materials are included in parts by weight: 35-45 parts of styrene, 15-20 parts of methyl methacrylate, 20-30 parts of butyl acrylate, 8-12 parts of mercaptan-modified acrylonitrile, 650-750 parts of water, 5-7 parts of emulsifier and 0.8-1.2 parts of initiator; Among them, the emulsifier is divided into a first emulsifier, a second emulsifier and a third emulsifier; the initiator is divided into a first initiator, a second initiator and a third initiator.

[0020] Preferably, the following raw materials in parts by weight are also included: 4-6 parts of ethyl 3-aminocrotonate; The raw materials of the mercaptan-modified acrylonitrile include 15-20 parts of acrylonitrile, 0.2-1 parts of o-aminobenzenethiol and 0.1-0.2 parts of azobisisobutyronitrile.

[0021] The above technical solution of the present invention includes at least the following beneficial effects: (1) The benzene ring in styrene acts as a rigid group, which can improve the mechanical strength and thermal stability of the copolymer. The methyl methacrylate skeleton has a high density of CC bonds, which gives the copolymer higher hardness, scratch resistance and impact resistance. In addition, methyl methacrylate is relatively stable under the action of ultraviolet light and oxygen, reducing the aging rate of the polymer. The long-chain alkyl structure of butyl acrylate reduces the rigidity and glass transition temperature of the polymer, improves the toughness of the polymer, and significantly improves the impact resistance of the polymer, avoiding the reduction of impact resistance of the copolymer due to excessive rigidity.

[0022] (2) By introducing o-aminobenzenethiol and utilizing its amino and thiol functional groups, the modified acrylonitrile has better compatibility and reactivity with other monomers in the subsequent copolymerization reaction, thereby enhancing the cross-linking ability of the modified acrylonitrile and improving the interaction between the molecular chains, thereby improving the heat resistance and chemical corrosion resistance of the copolymer.

[0023] (3) By adopting the process of adding emulsifier in stages, the stability of the emulsion in the early, middle and late stages of the reaction is ensured, the monomer or polymer stratification is prevented, and the overall uniform distribution of the latex is promoted, which helps to improve the physical properties of the copolymer. The staged addition of the initiator is conducive to the continuous reaction at different stages, avoiding the problem of too fast or uneven reaction rate caused by adding the initiator all at once. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described in combination with the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.

[0025] Example 1 Take 20 parts of acrylonitrile and 1 part of o-aminobenzenethiol, add them to the solvent dimethyl sulfoxide, then add 0.15 parts of azobisisobutyronitrile, pass nitrogen, heat to 60°C, and stir at 350r / min for 24h, settle, wash, and dry to obtain o-aminobenzenethiol-modified acrylonitrile.

[0026] The emulsifier used was 6 parts of sodium dodecyl sulfate, which was divided into 4.5 parts of the first emulsifier, 0.9 parts of the second emulsifier and 0.6 parts of the third emulsifier. The initiator used was 1 part of potassium persulfate, which was divided into 0.55 parts of the first initiator, 0.3 parts of the second initiator and 0.15 parts of the third initiator.

[0027] 700 parts of water and the first emulsifier were added into the reactor, the temperature was raised to 80°C, stirring was started at 400 r / min, 40 parts of styrene and the first initiator were added, and the reaction was continued for 2.5 hours. Then, 20 parts of methyl methacrylate, 25 parts of butyl acrylate, the second emulsifier and the second initiator were added. The temperature was kept constant, stirring was continued at 350 r / min, and the reaction was continued for 5 hours. Finally, 10 parts of modified acrylonitrile, 4 parts of ethyl 3-aminocrotonate, the third emulsifier and the third initiator were added, and the reaction was continued at 330 r / min for 3 hours to obtain an acrylic copolymer emulsion, which was spray-dried at 240°C to obtain an acrylic ester copolymer.

[0028] Example 2 Take 18 parts of acrylonitrile and 0.6 parts of o-aminobenzenethiol, add them to the solvent dimethyl sulfoxide, then add 0.15 parts of azobisisobutyronitrile, pass nitrogen, heat to 62°C, and stir at a speed of 330r / min for 24h, settle, wash, and dry to obtain o-aminobenzenethiol-modified acrylonitrile.

[0029] The emulsifier used was 7 parts of sodium dodecylbenzene sulfonate, which was divided into 5.6 parts of the first emulsifier, 0.7 parts of the second emulsifier and 0.7 parts of the third emulsifier. The initiator used was 1.2 parts of sodium persulfate, which was divided into 0.72 parts of the first initiator, 0.3 parts of the second initiator and 0.18 parts of the third initiator.

[0030] 680 parts of water and the first emulsifier were added into the reactor, the temperature was raised to 78°C, stirring was started at a speed of 380 r / min, 42 parts of styrene and the first initiator were added, and the reaction was continued for 3 hours. Then, 18 parts of methyl methacrylate, 30 parts of butyl acrylate, the second emulsifier and the second initiator were added, the temperature was kept constant, stirring was continued at a speed of 300 r / min, and the reaction was continued for 3 hours. Finally, 8 parts of modified acrylonitrile, 6 parts of ethyl 3-aminocrotonate, the third emulsifier and the third initiator were added, and the reaction was continued at a speed of 300 r / min for 2 hours to obtain an acrylic copolymer emulsion, which was spray-dried at 220°C to obtain an acrylic ester copolymer.

[0031] Example 3 Take 16 parts of acrylonitrile and 1 part of o-aminobenzenethiol, add them to the solvent dimethyl sulfoxide, then add 0.1 parts of azobisisobutyronitrile, pass nitrogen, heat to 65°C, and stir at a speed of 380r / min for 23h. After sedimentation, wash and dry, o-aminobenzenethiol modified acrylonitrile is obtained.

[0032] 5 parts of sodium dodecylbenzene sulfonate are used, which are divided into 3.5 parts of the first emulsifier, 0.75 parts of the second emulsifier and 0.75 parts of the third emulsifier. 0.9 parts of initiator ammonium persulfate are used, which are divided into 0.45 parts of the first initiator, 0.27 parts of the second initiator and 0.18 parts of the third initiator.

[0033] 750 parts of water and the first emulsifier were added into the reactor, the temperature was raised to 75°C, stirring was started at a speed of 420 r / min, 38 parts of styrene and the first initiator were added, and after reacting for 2 hours, 15 parts of methyl methacrylate, 22 parts of butyl acrylate, the second emulsifier and the second initiator were added, the temperature was kept constant, stirring was performed at a speed of 400 r / min, and the reaction was performed for 4 hours. Finally, 11 parts of modified acrylonitrile, 5 parts of ethyl 3-aminocrotonate, the third emulsifier and the third initiator were added, and the reaction was stirred at a speed of 250 r / min for 3 hours to obtain an acrylic copolymer emulsion, which was spray-dried at 230°C to obtain an acrylic ester copolymer.

[0034] Example 4 Take 19 parts of acrylonitrile and 0.2 parts of o-aminobenzenethiol, add them to the solvent dimethyl sulfoxide, then add 0.2 parts of azobisisobutyronitrile, pass nitrogen, heat to 60°C, and stir at 400r / min for 23h. After sedimentation, wash and dry, o-aminobenzenethiol modified acrylonitrile is obtained.

[0035] The emulsifier sodium dodecyl sulfate is used in an amount of 7 parts, which is divided into 5.25 parts of the first emulsifier, 0.7 parts of the second emulsifier and 1.05 parts of the third emulsifier. The initiator sodium persulfate is used in an amount of 1 part, which is divided into 0.5 parts of the first initiator, 0.25 parts of the second initiator and 0.25 parts of the third initiator.

[0036] 720 parts of water and the first emulsifier were added into the reactor, the temperature was raised to 76°C, stirring was started at a speed of 450 r / min, 35 parts of styrene and the first initiator were added, and the reaction was continued for 2.5 hours. Then, 16 parts of methyl methacrylate, 28 parts of butyl acrylate, the second emulsifier and the second initiator were added. The temperature was kept constant, stirring was continued at a speed of 380 r / min, and the reaction was continued for 3.5 hours. Finally, 10 parts of modified acrylonitrile, 6 parts of ethyl 3-aminocrotonate, the third emulsifier and the third initiator were added, and the reaction was continued at a speed of 350 r / min for 2.5 hours to obtain an acrylic copolymer emulsion, which was spray-dried at 200°C to obtain an acrylic ester copolymer.

[0037] Example 5 Take 15 parts of acrylonitrile and 0.3 parts of o-aminobenzenethiol, add them to the solvent dimethyl sulfoxide, then add 0.1 parts of azobisisobutyronitrile, pass nitrogen, heat to 55°C, and stir at a speed of 300r / min for 25h. After sedimentation, wash and dry, o-aminobenzenethiol modified acrylonitrile is obtained.

[0038] 6 parts of sodium dodecylbenzene sulfonate were used as emulsifier, which was divided into 4.5 parts of first emulsifier, 0.7 parts of second emulsifier and 0.8 parts of third emulsifier. 0.8 parts of potassium persulfate were used as initiator, which was divided into 0.44 parts of first initiator, 0.2 parts of second initiator and 0.16 parts of third initiator.

[0039] 650 parts of water and the first emulsifier were added into the reactor, the temperature was raised to 80°C, stirring was started at a speed of 350 r / min, 45 parts of styrene and the first initiator were added, and the reaction was continued for 2 hours. Then, 19 parts of methyl methacrylate, 20 parts of butyl acrylate, the second emulsifier and the second initiator were added, the temperature was kept constant, stirring was continued at a speed of 330 r / min, and the reaction was continued for 4.5 hours. Finally, 9 parts of modified acrylonitrile, 4 parts of ethyl 3-aminocrotonate, the third emulsifier and the third initiator were added, and the reaction was continued at a speed of 280 r / min for 2 hours to obtain an acrylic copolymer emulsion, which was spray-dried at 210°C to obtain an acrylic ester copolymer.

[0040] Example 6 Take 17 parts of acrylonitrile and 0.7 parts of o-aminobenzenethiol, add them to the solvent dimethyl sulfoxide, then add 0.15 parts of azobisisobutyronitrile, pass nitrogen, heat to 58°C, and stir at a speed of 350r / min for 23h. After sedimentation, wash and dry, o-aminobenzenethiol modified acrylonitrile is obtained.

[0041] 7 parts of sodium dodecyl sulfate emulsifier was used, which was divided into 4.9 parts of the first emulsifier, 1.05 parts of the second emulsifier and 1.05 parts of the third emulsifier. 1 part of ammonium persulfate initiator was used, which was divided into 0.5 parts of the first initiator, 0.3 parts of the second initiator and 0.2 parts of the third initiator.

[0042] 680 parts of water and the first emulsifier were added into the reactor, the temperature was raised to 77°C, stirring was started at a speed of 380 r / min, 42 parts of styrene and the first initiator were added, and the reaction was continued for 3 hours. Then, 20 parts of methyl methacrylate, 25 parts of butyl acrylate, the second emulsifier and the second initiator were added, the temperature was kept constant, stirring was continued at a speed of 370 r / min, and the reaction was continued for 4 hours. Finally, 12 parts of modified acrylonitrile, 4 parts of ethyl 3-aminocrotonate, the third emulsifier and the third initiator were added, and the reaction was continued at a speed of 300 r / min for 2 hours to obtain an acrylic copolymer emulsion, which was spray-dried at 220°C to obtain an acrylic ester copolymer.

[0043] Example 7 Take 20 parts of acrylonitrile and 0.8 parts of o-aminobenzenethiol, add them to the solvent dimethyl sulfoxide, then add 0.2 parts of azobisisobutyronitrile, pass nitrogen, heat to 62°C, and stir at a speed of 380r / min for 23h. After sedimentation, wash and dry, o-aminobenzenethiol modified acrylonitrile is obtained.

[0044] 5 parts of sodium dodecylbenzene sulfonate were used as emulsifier, which was divided into 3.75 parts of first emulsifier, 0.5 parts of second emulsifier and 0.75 parts of third emulsifier. 1.2 parts of sodium persulfate were used as initiator, which was divided into 0.6 parts of first initiator, 0.42 parts of second initiator and 0.18 parts of third initiator.

[0045] 720 parts of water and the first emulsifier were added into the reactor, the temperature was raised to 75°C, stirring was started at a speed of 420 r / min, 38 parts of styrene and the first initiator were added, and the reaction was continued for 2 hours. Then, 18 parts of methyl methacrylate, 28 parts of butyl acrylate, the second emulsifier and the second initiator were added, the temperature was kept constant, stirring was continued at a speed of 320 r / min, and the reaction was continued for 3 hours. Finally, 11 parts of modified acrylonitrile, 5 parts of ethyl 3-aminocrotonate, the third emulsifier and the third initiator were added, and the reaction was continued at a speed of 280 r / min for 3 hours to obtain an acrylic copolymer emulsion, which was spray-dried at 230°C to obtain an acrylic ester copolymer.

[0046] Example 8 Take 20 parts of acrylonitrile and 1 part of o-aminobenzenethiol, add them to the solvent dimethyl sulfoxide, then add 0.15 parts of azobisisobutyronitrile, pass nitrogen, heat to 60°C, and stir at 350r / min for 24h, settle, wash, and dry to obtain o-aminobenzenethiol-modified acrylonitrile.

[0047] The emulsifier used was 6 parts of sodium dodecyl sulfate, which was divided into 4.5 parts of the first emulsifier, 0.9 parts of the second emulsifier and 0.6 parts of the third emulsifier. The initiator used was 1 part of potassium persulfate, which was divided into 0.55 parts of the first initiator, 0.3 parts of the second initiator and 0.15 parts of the third initiator.

[0048] 700 parts of water and the first emulsifier were added into the reactor, the temperature was raised to 80°C, stirring was started at 400 r / min, 40 parts of styrene and the first initiator were added, and the reaction was continued for 2.5 hours. Then, 20 parts of methyl methacrylate, 25 parts of butyl acrylate, the second emulsifier and the second initiator were added. The temperature was kept constant, stirring was continued at 350 r / min, and the reaction was continued for 5 hours. Finally, 10 parts of modified acrylonitrile, the third emulsifier and the third initiator were added, and the reaction was continued at 330 r / min for 3 hours to obtain an acrylic copolymer emulsion, which was spray-dried at 240°C to obtain an acrylic ester copolymer.

[0049] The present invention also carries out comparative examples and related tests.

[0050] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that o-aminobenzenethiol is not used to modify acrylonitrile, but acrylonitrile is used instead of mercaptan to modify acrylonitrile. Other compositions and preparation methods are the same as those of Example 1.

[0051] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that when water is added to the reactor, the emulsifier is added once and not added subsequently; when styrene is added, the initiator is added once and not added subsequently. The other compositions and preparation methods are the same as those of Example 1.

[0052] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that styrene is used instead of methyl methacrylate and butyl acrylate, and the other compositions and preparation methods are the same as those of Example 1.

[0053] Performance testing The acrylic acid ester copolymers prepared in Examples 1-8 and Comparative Examples 1-3 were used to prepare thermoplastic rubber, and the obtained thermoplastic rubber was subjected to performance test according to the following standards.

[0054] The aging test was carried out according to GB / T3512-2014 vulcanized rubber or thermoplastic rubber hot air accelerated aging and heat resistance test, and the test results were expressed as the hardness change rate; the tensile strength and elongation at break test were carried out according to GB / T6037-1985 vulcanized rubber high temperature tensile strength and elongation at break test; the impact strength test was carried out according to GB / T1043.1-2008 standard simply supported beam; the heat deformation temperature (1.80MPa) was tested according to GB / T1634.1-2004, and the test results are shown in Table 1 below.

[0055] Table 1

[0056] It can be seen from the results in Table 1 above that compared with Example 1, the copolymer prepared in Comparative Example 1 has a significantly lower heat deformation temperature, indicating that o-aminobenzenethiol-modified acrylonitrile is beneficial to the improvement of the heat resistance of the copolymer and the enhancement of the thermal stability of the copolymer; compared with the copolymer prepared in Example 1, the copolymer prepared in Comparative Example 2 has significantly lower properties, indicating that the segmented addition of emulsifier and initiator is beneficial to the uniform distribution of the emulsion and the continuous copolymerization reaction, so that the hardness, toughness and other properties of the prepared copolymer are improved; compared with the copolymer prepared in Example 1, the copolymer prepared in Comparative Example 3 has a higher aging resistance. The hardness change rate, impact strength reflecting impact resistance, and tensile strength reflecting toughness show a more obvious decline. It can be seen that the addition of methyl methacrylate and butyl acrylate is beneficial to the improvement of aging resistance and toughness of the polymer, and can avoid the performance defects caused by high rigidity and low toughness of the polymer; the difference between Example 8 and Example 1 is that 3-aminoethyl crotonate is not used in Example 8, which leads to a general decline in the hardness change rate, heat deformation temperature, elongation at break rate and other properties of the polymer. This shows that the addition of 3-aminoethyl crotonate can make the hardness and toughness of the polymer more balanced and can improve the aging resistance of the copolymer.

[0057] The above are preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A method for preparing an acrylic acid ester copolymer, characterized in that: The following steps are involved: Step S1, preparation of mercaptan-modified acrylonitrile: Adding acrylonitrile and o-aminobenzenethiol to a solvent, and then adding azobisisobutyronitrile, heating and stirring under a nitrogen environment, settling, washing, and drying to obtain mercaptan-modified acrylonitrile; Step S2, preparation of acrylate copolymer: Add water and the first emulsifier into a reaction kettle, heat up and stir, add styrene and the first initiator, then add methyl methacrylate, butyl acrylate, the second emulsifier and the second initiator, keep the temperature constant and continue stirring, finally add thiol-modified acrylonitrile, the third emulsifier and the third initiator, continue stirring to obtain an acrylic copolymer emulsion, spray dry and obtain an acrylate copolymer.

2. The method for preparing an acrylic acid ester copolymer according to claim 1, characterized in that: In step S1, the heating and stirring temperature is 55-65° C., the speed is 300-400 r / min, and the time is 23-25 ​​h; and the solvent is dimethyl sulfoxide.

3. The method for preparing an acrylic acid ester copolymer according to claim 1, characterized in that: The ratio of the first emulsifier, the second emulsifier and the third emulsifier is (7-8): (1-1.5): (1-1.5).

4. The method for preparing an acrylic acid ester copolymer according to claim 1, characterized in that: The ratio of the first initiator, the second initiator and the third initiator is (5-6): (2.5-3.5): (1.5-2.5).

5. The method for preparing an acrylic acid ester copolymer according to claim 1, characterized in that: The first emulsifier, the second emulsifier and the third emulsifier are all one of sodium dodecyl sulfate and sodium dodecylbenzene sulfonate; the first initiator, the second initiator and the third initiator are all one of potassium persulfate, sodium persulfate and ammonium persulfate.

6. The method for preparing an acrylic acid ester copolymer according to claim 1, characterized in that: In step S2, the temperature of the heating and stirring is 75-80°C, the speed is 350-450r / min, and the time is 2-3h; the speed of continued stirring is 300-400r / min, and the time is 3-5h.

7. The method for preparing an acrylic acid ester copolymer according to claim 1, characterized in that: In the step S2, ethyl 3-aminocrotonate is added before continuous stirring; the continuous stirring speed is 250-350 r / min, and the time is 2-3 h.

8. The method for preparing an acrylic acid ester copolymer according to claim 1, characterized in that: In step S2, the spray drying temperature is 200-210°C.

9. The method for preparing an acrylic acid ester copolymer according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 35-45 parts of styrene, 15-20 parts of methyl methacrylate, 20-30 parts of butyl acrylate, 8-12 parts of mercaptan-modified acrylonitrile, 650-750 parts of water, 5-7 parts of emulsifier and 0.8-1.2 parts of initiator; Among them, the emulsifier is divided into a first emulsifier, a second emulsifier and a third emulsifier; the initiator is divided into a first initiator, a second initiator and a third initiator.

10. The method for preparing an acrylic acid ester copolymer according to claim 9, characterized in that: Also includes the following raw materials in parts by weight: 4-6 parts of ethyl 3-aminocrotonate; The raw materials of the mercaptan-modified acrylonitrile include 15-20 parts of acrylonitrile, 0.2-1 parts of o-aminobenzenethiol and 0.1-0.2 parts of azobisisobutyronitrile.

Citation Information

Patent Citations

  • A kind of high resilience water-based acrylic ester composition and preparation method thereof

    CN114591474B

  • Acrylate elastic emulsion with excellent low-temperature breaking elongation and preparation method thereof

    CN106632823A

  • Acrylate-styrene-acrylonitrile grafted copolymer and production method thereof

    CN109867749A

  • Phase change heat storage material elastic film and preparation method thereof

    CN115322511A

  • Thermoplastic resin composition

    JP1994299023A